SISTEM OLAH TANAH TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG (Zea mays L.) - Wira Hadianto; Nana Ariska; Muhammad Husen (Jurnal Agrotek Lestari, 2019)
This study aims to determine the effect of tillage systems on the growth and production of corn. Materials and tools used in this study were: Corn seeds used in this study were Bonanza F1 Varieties, the basic fertilizer used was NPK BASF (15:15:15) 300 kg ha-1. The tools that will be used in this study are Scales, Caliper, Machetes, Hoes, Knives, Meters, Gembor, Buckets, Hend spayers and stationery. The experimental design used in this study was a non factorial randomized block design (RBD) 3 treatments with 3 replications. The factors studied include: Soil processing system (T) which consists of 3 (three) levels including: No Soil (T1), Minimum Soil (T2) and Maximum Soil (T3). Observation parameters observed were plant height, stem diameter, ear length, ear diameter, ear weight, ear weight per plot and ear weight per ha. The results showed that the tillage system had a very significant effect on plant height at the age of 21 HST, weight of crop cobs, weight of cobs per plot and weight of cobs per hectare. Significantly affected plant height at ages 28, 35 and 42 HST, stem diameter age 21.28, 35 and 42, but had no significant effect on cob length and ear diameter. The best treatment is found in the maximum tillage system (T3). Keywords: tillage system, corn, Bonanza F1 variety